“Block D” Phenomenon in Hemolytic Disease of Fetus and Newborn: The Immunohematological Implications - Sourav Mukherjee; Sudipta Sekhar Das; Sourav Chowdhury (Global Journal of Transfusion Medicine)
Background and Objectives: “Block D” in hemolytic disease of the fetus and newborn (HDFN) is quite rare and should be evaluated meticulously. We analyzed “Block D” phenomenon in neonates with HDFN due to rhesus (Rh) incompatibilities. The objective of this study was to identify the blocking phenomenon in HDFN by simple, sensitive methods so that they can be implemented in routine practices. Methods: The study was conducted over 10 years, and written informed consent was taken from each participating parent/guardian. Detailed immunohematological workup for “Block D” was done on 11 samples. Complete patient details were obtained from the hospital information system. All laboratory parameters of neonates were observed till discharge from the hospital. Results: All mothers were Rh-D negative with a median age of 28 years. All of them revealed anti-Rh-D antibodies in their serum with titer ranging from 256 to 1024. All neonatal red cells were direct antiglobulin test (DAT) positive and initially Rh-D negative. Rh-D typing on eluted red cells confirmed the presence of D antigen. Strong positive and negative correlations were observed between newborn anti-D immunoglobulin G titer and newborn DAT (r = +0.71, P = 0.031) and newborn DAT and newborn hemoglobin (Hb) (r = −0.78, P = 0.032), respectively. While all neonates received phototherapy, four of them also received exchange transfusion. Gradual increase in mean Hb and decrease in both total serum bilirubin and DAT were observed from day 0 to day 7 (P < 0.05). Conclusion: “Block D” though uncommon signifies the severity of HDFN. Often this phenomenon is missed due to a lack of standard protocol. Through detailed immunohematological characterizations, we could develop a diagnostic pathway to confirm “Block D” in HDFN which can be easily established in the resource-constrained laboratories.